Effects of sex and deletion of neuropeptide Y2 receptors from GABAergic neurons on affective and alcohol drinking behaviors in mice - McCall, Nora M.; Sprow, Gretchen M.; Delpire, Eric; Thiele, Todd E.; Kash, Thomas L.; Pleil, Kristen E. (Frontiers in Integrative Neuroscience, 2013)
A large literature has demonstrated that neuropeptide Y (NPY) regulates many emotional and reward-related behaviors via its primary receptors, Y1R and Y2R. Classically, NPY actions at postsynaptic Y1R decrease anxiety, depression, and alcohol drinking, while its actions at presynaptic Y2R produce the opposite behavioral phenotypes. However, emerging evidence suggests that activation of Y2R can also produce anxiolysis in a brain region and neurotransmitter system-dependent fashion. Further, numerous human and rodent studies have reported that females display higher levels of anxiety, depression, and alcohol drinking. In this study, we evaluated sex differences and the role of Y2R on GABAergic transmission in these behaviors using a novel transgenic mouse that lacks Y2R specifically in VGAT-expressing neurons (VGAT-Y2R knockout). First, we confirmed our genetic manipulation by demonstrating that Y2R protein expression was decreased and that a Y2R agonist could not alter GABAergic transmission in the extended amygdala, a limbic brain region critically implicated in the regulation of anxiety and alcohol drinking behaviors, using immunofluorescence and slice electrophysiology. Then, we tested male and female VGAT-Y2R knockout mice on a series of behavioral assays for anxiety, depression, fear, anhedonia, and alcohol drinking. We found that females displayed greater basal anxiety, higher levels of ethanol consumption, and faster fear conditioning than males, and that knockout mice exhibited enhanced depressive-like behavior in the forced swim test. Together, these results confirm previous studies that demonstrate higher expression of negative affective and alcohol drinking behaviors in females than males, and they highlight the importance of Y2R function in GABAergic systems in the expression of depressive-like behavior.